Trends of Banana Production among Smallholders’ Farmers Due to Rainfall and Temperature variations in Mount Kenya Region County, Kenya - David K. Karienye; Hellen Kamiri (Budapest International Research and Critics University, 2020)
Unreliability and unpredictability of rainfall amount and temperature fluctuations have negative impact on agriculture production especially in Africa where coping mechanisms are limited. The future of rainfed agriculture is uncertain more so on banana production among the smallholder’s farmers due to climate variability. This study examined the extent of rainfall and temperature changes on banana production among smallholders’ farmers in Mount. Kenya region of Kenya from 2009 and 2017. The sites were purposively selected to include Imenti south (Meru County) and Mukurweini sub-counties (Nyeri County) where banana production has been practiced since 1990. A sample size of 381 respondents was identified using simple random sampling. Production and climatic (rainfall and Temperature) data were sourced from Horticultural Crop Directorate and Kenya Meteorological Department respectively for the stations adjacent to the study sites for the study period. Results showed decreasing trends on rainfall amounts while temperature increasing trend. Study found that rainfall increase does not necessarily translate to increased production while temperature level of about 18.50C gave the maximum yields. Majority of the respondents (42.8%) in the study region admitted to have changed the land use and type of crops they have been farming during the study period whereas 30% changed from other crops to banana farming. Banana acreage and production in both sub-counties have been increasing during the study period. The County and National government should provide irrigation as a coping mechanism to banana production due to the declining rainfall and increasing temperature in the region. We recommended provision of weather information on the onset of the rainfall period and distribution within the seasons in order to respond to the effects of climate variability.